Da sensibilização à proteção : aplicação da Política de Segurança da Informação, um estudo de caso na UnB - Fernandes, Rodrigo Ildson Lima (2025)
This study addresses the issue of contractual default in the Brazilian public sector, specifically in the context of the Superior Court of Justice (STJ). The scientific and social relevance of the topic is tied to the need for innovation and effective governance in public procurement, considering the challenges posed by Law 14.133/2021. The main objective is to identify how economic and financial information can anticipate the risk of contractual default through the Supplier (Dis)Trust Index (IDF). The research employs a statistical model based on logistic regression, analyzing contract data from the STJ between 2018 and 2023. The theoretical framework includes studies on public procurement, evidence-based management, and predictive models of insolvency. The primary finding is that the IDF, by using a combination of economic, financial, and legal variables, provides a prediction of default with high sensitivity and overall accuracy. The main technical-technological product is an automated statistical analysis script in Stata® software, which allows the practical application of the predictive model in other public institutions. It is concluded that the IDF is an effective tool for risk management in public contracts, recommended for use during the contract execution phase rather than as a qualification criterion.